Firms persistence under sanctions: Micro-level evidence from Iran - Iman Cheratian; Saleh Goltabar; Mohammad Reza Farzanegan (The World Economy, 2023)
Given the importance of firm strategic management in the time of crisis, this study investigates Micro, Small and Medium Enterprises (MSMEs) approaches to persistence during the international sanctions against Iran. Using data from a questionnaire of 486 firms between December 2019 and September 2020, we found that reducing research and development (R&D) expenditures, marketing costs and fixed/overhead costs and investing in information technology (IT) are positively related to firm persistence. Conversely, managerial decisions to reduce production and cut or freeze staff pay have negative and significant impacts on a firm's ability to persist during sanctions. Moreover, micro-firms are more resilient than their small and medium counterparts. The findings also confirm that age has a significant and positive impact on firm persistence. Finally, the results show that having a business plan, access to finance and technology, owner education, export orientation, business networking and consulting services are the key drivers of withstanding pressure from sanctions.
Keywords: 330; crisis; firm; Iran; management; ordered probit; persistence; recession; sanction